ANALISIS PENGELOLAAN DANA DESA DALAM PELAKSANAAN PEMBANGUNAN TAHUN ANGGARAN 2020 (STUDI PADA DESA WAMBOULE KABUPATEN BUTON UTARA) - Suriyani BB; Liwaul Liwaul; Gita Listafila (Universitas Halu Oleo, 2022)
This study aims to describe the management of village funds in the village of Wamboule, North Buton Regency and to describe the implementation of the development of the village of Wamboule, North Buton Regency. The data analysis method used in this research is descriptive qualitative. This study uses data sourced from primary and secondary data. The results of this study state that the management of village funds in Wamboule village, North Buton Regency can be said to be good based on three indicators, namely planning, implementation and accountability in accordance with the mandate of Government Regulation of the Republic of Indonesia Number 8 of 2016 concerning the second Amendment to Government Regulation of the Republic of Indonesia Number 60 of 2014 concerning Village Funds sourced from the State Budget and Expenditure Revenue. The implementation of the development of the Wamboule village, North Buton Regency in 2020 is going well based on the aspect of development and the use of the budget in accordance with the plan. In the implementation of development, the Wamboule village government always involves the community in both physical and non-physical development.